Accelerated aging effects on surface hardness and roughness of lingual retainer adhesives - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2008)
Objective: To test the null hypothesis that accelerated aging has no effect on the surface microhardness and roughness of two light-cured lingual retainer adhesives. Materials and Methods: Ten samples of light-cured materials, Transbond Lingual Retainer (3M Unitek) and Light Cure Retainer (Reliance) were cured with a halogen light for 40 seconds. Vickers hardness and surface roughness were measured before and after accelerated aging of 300 hours in a weathering tester. Differences between mean values were analyzed for statistical significance using a Hest. The level of statistical significance was set at P < .05. Results: The mean Vickers hardness of Transbond Lingual Retainer was 62.8 +/- 3.5 and 79.6 +/- 4.9 before and after aging, respectively. The mean Vickers hardness of Light Cure Retainer was 40.3 +/- 2.6 and 58.3 +/- 4.3 before and after aging, respectively. Differences in both groups were statistically significant (P < .001). Following aging, mean surface roughness was changed from 0.039 mu m to 0.121 mu m and from 0.021 mu m to 0.031 mu m for Transbond Lingual Retainer and Light Cure Retainer, respectively. The roughening of Transbond Lingual Retainer with aging was statistically significant (P < .05), while the change in the surface roughness of Light Cure Retainer was not (P > .05). Conclusions: Accelerated aging significantly increased the surface microhardness of both light-cured retainer adhesives tested. It also significantly increased the surface roughness of the Transbond Lingual Retainer.
Keywords: orthodontic adhesives; orthodontic retainer; aging; surface hardness; surface roughness; SOFT DENTURE LINERS; COMPOSITE RESTORATIVE MATERIALS; COLOR STABILITY; DENTAL COMPOSITES; ORTHODONTIC ADHESIVES; WEAR-RESISTANCE; GLASS-IONOMER; WATER; RESINS; DEGRADATION